F136. Quantitative EEG offers potential utility of biomarkers for non-dopaminergic disease severity in Parkinson's disease. (May 2018) - Geraedts, Victor; Marinus, J.; Gouw, Alida; Mosch, Arne; Stam, Cornelis; van Hilten, Bob; Contarino, M.F.; Tannemaat, Martijn
Abstract : Introduction: Parkinson's Disease (PD) patients are eligible for Deep Brain Stimulation (DBS) when oral medication offers insufficient benefit; however, accurate assessment of disease severity is crucial as non-dopaminergic features may deteriorate post-operatively. There is currently no reliable biomarker for non-dopaminergic disease severity. We therefore aimed to investigate whether quantitative EEG reflects non-dopaminergic disease severity. Methods: Sixty-three consecutive PD patients screened for DBS between September 2015 and July 2017 were included (mean age 62.4 ± 7.2 years, 32% females). Relative spectral powers and the Phase-Lag-Index (PLI) reflecting functional connectivity were analysed.. The SENS-PD score and its subdomains quantified non-dopaminergic disease severity, whereas the MDS-UPDRS III quantified motor-severity. Results: The SENS-PD composite score correlated with a spectral ratio ( δ + θ / α 1 + α 1 + β powers) (global spectral ratio Pearson r = 0.4, 95% Confidence Interval (95%CI) 0.1 to 0.6), as well as PLI in the α 2 band (10–13 Hz) (r = −0.3, 95%CI −0.5 to −0.1). These correlations seem driven by cognition (global spectral ratio: r = 0.4, 95%CI 0.2 to 0.6; global α 2 PLI r = −0.3, 95%CI −0.5 to −0.2) and psychotic symptoms (global spectral ratio: r = 0.5, 95%CI 0.2 to 0.8; global α 2 PLI: r = −0.2, 95%CI −0.3 to 0.0). MDS-UPDRS III was not significantly correlated with EEG parameters. Conclusion: Both EEG slowing and reduced functional connectivity in the α 2 band were associated with advanced non-dopaminergic disease severity in PD. Further study is needed to evaluate the complementary utility of EEG parameters as a predictive tool of non-dopaminergic involvement in PD.